KORELASI MOTIVASI BELAJAR DAN GAYA BELAJAR DENGAN PRESTASI BELAJAR ILMU ALAMIAH DASAR MAHASISWA PRODI PGSD - Grahito Wicaksono, Anggit (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study was to determine: (1) the existence of positive and significant relationship between learning motivation and learning achievement in basic natural science subjects; (2) there is a positive and significant relationship between learning styles and academic achievement basic natural science subjects; and (3) there is a positive and significant relationship together between learning motivation and learning styles with learning achievement in basic natural science subjects. This study used correlational and ex-post facto methods with multiple correlation analysis technique. The first hypothesis test results concluded that there is a positive and significant relationship between learning motivation and learning achievement in basic natural science subjects. The second hypothesis test results concluded that there is a positive and significant relationship between learning styles and academic achievement basic natural science subjects. Double correlation test results for the third hypothesis can be inferred learning motivation and learning styles together have a positive and significant relationship with achievement learn basic natural science subjects. The coefficient of determination of 0.398 indicates that 39.8% of the change in the learning achievement of the basic natural science subjects affected by learning motivation and learning styles, while 60.2% influenced by other variables not studied.